Desarda versus Lichenstein repair in treatment of inguinal hernia: our experience in KVG Medical College and Hospital - Ramu, Abhirup H.; Kenchetty, Priyanka; Chidananda, Aishwarya K. (International Surgery Journal, 2021)
Background: Desarda technique of inguinal hernia repair introduced in 2001 is still not considered standard tissue-based hernia repair technique. The aim of the study was to compare the tissue based Desarda technique with standard Lichtenstein repair in treatment of primary inguinal hernia. Methods: 72 cases were allocated into 2 groups. Desarda (D Group) had 36 and Lichtenstein (L Group) had 36 patients. Primary outcome factors included operative time measured from skin incision to skin closure. Post operative pain scores was using Sheffield scale. Ecchymosis, hematoma, seroma, surgical site infections, foreign body sensation etc. were evaluated as postoperative complications. A follow up examination was planned for 6 month to look for early recurrence (<6 month) and chronic groin pain. Results: Mean age in desarda’s group 44.94±15.5 years while Lichtenstein group was 45.47±13.12 years. The mean duration of surgery 42.83 min (D) versus 50.72 min (L). Duration of hospital stay 3.38 days (D) versus 4.08 days (L). Time taken to return to normal and work activities was significantly less in Desarda group (p=0.001). After 6-month mean follow up period 1 recurrence is noted in each arm (p=1). Conclusions: On comparison of Desarda with Lichtenstein repair. Desarda technique does not use a mesh. Patients after Desarda's operative procedure gets normal activity sooner as compared to the standard Lichtenstein mesh repair. Complications similar to standardized technique. We also found the use of Desarda technique in patients with indirect hernia is a technically sound option than Lichtenstein technique.